A Multiscale Understanding of the Thermodynamic and Kinetic Mechanisms of Laser Additive Manufacturing. (October 2017) - Gu, Dongdong; Ma, Chenglong; Xia, Mujian; Dai, Donghua; Shi, Qimin
Abstract: Selective laser melting (SLM) additive manufacturing (AM) technology has become an important option for the precise manufacturing of complex-shaped metallic parts with high performance. The SLM AM process involves complicated physicochemical phenomena, thermodynamic behavior, and phase transformation as a high-energy laser beam melts loose powder particles. This paper provides multiscale modeling and coordinated control for the SLM of metallic materials including an aluminum (Al)-based alloy (AlSi10Mg), a nickel (Ni)-based super-alloy (Inconel 718), and ceramic particle-reinforced Al-based and Ni-based composites. The migration and distribution mechanisms of aluminium nitride (AlN) particles in SLM-processed Al-based nanocomposites and the in situ formation of a gradient interface between the reinforcement and the matrix in SLM-processed tungsten carbide (WC)/Inconel 718 composites were studied in the microscale. The laser absorption and melting/densification behaviors of AlSi10Mg and Inconel 718 alloy powder were disclosed in the mesoscale. Finally, the stress development during line-by-line localized laser scanning and the parameter-dependent control methods for the deformation of SLM-processed composites were proposed in the macroscale. Multiscale numerical simulation and experimental verification methods are beneficial in monitoring the complicated powder-laser interaction, heat and mass transfer behavior, and microstructural and mechanical properties development during the SLM AM process.